Prefácio - Vasconcelos, Marcos da Cunha e Lorena Perestrello, 1971 (2023)
NATO e as relações transatlânticas : de Madrid a Vilnius / coordenação [de] José Matos Correia. - Lisboa : Universidade Lusíada. 2023. - 978-989-640-264-8. - P...-...